Dampak IPM, tingkat pengangguran dan tingkat kemiskinan terhadap ketimpangan pendapatan di Sumatera Bagian Selatan - Ersad, Muhamnad Ersad; Amir, Amri; Zulgani, Zulgani (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to analyze the development of the Human Development Index (HDI), Unemployment Rate, Poverty Levels in the Southern Sumatra Region, analyze the condition of regional development inequality in the Southern Sumatra Provinces and analyze the influence of the Human Development Index (IPM), Unemployment Rate, Level of Poverty on income inequality in southern Sumatra in 2010-2019. This research is a quantitative research. The data used is a cross section of 5 provinces in Southern Sumatra and time series for 2010-2019. The data is processed by panel data analysis with fixed effect regression model. Based on the results of the HDI panel data regression test, the unemployment rate and poverty rate have a significant effect on income in Southern Sumatra. All research variables have a simultaneous effect on income inequality. Partially, the HDI variable and the poverty level have no effect on income inequality, while from the research variable only the Unemployment Rate has a negative effect on income inequality.